2015
DOI: 10.1227/neu.0000000000000705
|View full text |Cite
|
Sign up to set email alerts
|

Altered Ulnar Nerve Kinematic Behavior in a Cadaver Model of Entrapment

Abstract: This work provides a framework for evaluating regional nerve kinematics. Suppressed translation due to tethering shifted the location of high strain from articular to more distal regions of the ulnar nerve. The authors hypothesize that deformation is thus shifted to a region of the nerve less accustomed to high strains, thereby contributing to the development of ulnar neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…A number of technical challenges remain. Most neural interfaces -even those composed of flexible thin-films like polyimide (here and ref (Hiebl et al, 2010;Lago et al, 2007;Seo et al, 2016)) and parylene (Caravaca et al, 2017;Chamanzar et al, 2015) -present elastic moduli substantially above the kilopascal-range of the host tissues (Mahan et al, 2015;Novak et al, 2012;Patel et al, 1998), aggravating long-term reactive responses and limiting interface longevity. High-resolution 3D printing offers the possibility of orthogonalizing the mechanical and material properties of an object, such that pliable microscale structures can be created from materials that are otherwise stiff and rigid (Bückmann et al, 2012(Bückmann et al, , 2014.…”
Section: Discussionmentioning
confidence: 82%
“…A number of technical challenges remain. Most neural interfaces -even those composed of flexible thin-films like polyimide (here and ref (Hiebl et al, 2010;Lago et al, 2007;Seo et al, 2016)) and parylene (Caravaca et al, 2017;Chamanzar et al, 2015) -present elastic moduli substantially above the kilopascal-range of the host tissues (Mahan et al, 2015;Novak et al, 2012;Patel et al, 1998), aggravating long-term reactive responses and limiting interface longevity. High-resolution 3D printing offers the possibility of orthogonalizing the mechanical and material properties of an object, such that pliable microscale structures can be created from materials that are otherwise stiff and rigid (Bückmann et al, 2012(Bückmann et al, , 2014.…”
Section: Discussionmentioning
confidence: 82%
“…Previous studies in median and ulnar nerves in rat models and humans revealed higher strains in the joint regions of the nerve, with maximum strains ranging from 20% to 30%. We observed similar distributions and magnitudes of maximum strain in both median and ulnar nerves at the elbow, most prominently in the region just distal to the joint (region D‐J; Fig.…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, nerves must maintain sufficient compliance to maintain their physiological functions . Compounding their biomechanical challenge, nerves undergo especially high epineurial strains—and a corresponding increase in compliance—near joints, as reported in a number of animal and human models . In fact, simple tasks such as elbow flexion can introduce ulnar nerve strains of 10%–15% in the human forearm, but 30% in the elbow .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, wrist extension slightly enhanced the classification performance of the CSA (AUC, 0.885), consistent with a trend toward a higher CSA with wrist extension (Table ). This may be a consequence of local nerve tethering at or just distal to the imaging location, which would serve to exaggerate deformation in regions distal to the stretch . Accordingly, control nerves slightly (though not significantly) reduced their CSA with wrist extension, consistent with nerve stretching.…”
Section: Discussionmentioning
confidence: 89%